2021
DOI: 10.21037/tlcr-20-1132
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative comparison of video-assisted thoracic surgery and open lobectomy for pT1-stage non-small cell lung cancer patients in China: a multi-center propensity score-matched analysis

et al.

Abstract: Background: Compared with open surgery, video-assisted thoracic surgery (VATS) has innovated the concept of the minimally invasive approach for non-small cell lung cancer (NSCLC) patients in past decades. This present study aimed to compare the perioperative and lymph node dissection outcomes between VATS lobectomy and open lobectomy for pathological stage T1 (pT1) NSCLC patients from both surgical and oncologic perspectives. Methods: This was a retrospective multicenter study. Patients who underwent surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, the average number of total and N2 lymph nodes resected in the VATS group was both lower than in the open thoracotomy group. Retrospective multicenter studies ( 11 , 20 ) have reported that although there is a reduced average number of resected lymph nodes during VATS, long-term survival is still better than open thoracotomy. Zhang et al ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the average number of total and N2 lymph nodes resected in the VATS group was both lower than in the open thoracotomy group. Retrospective multicenter studies ( 11 , 20 ) have reported that although there is a reduced average number of resected lymph nodes during VATS, long-term survival is still better than open thoracotomy. Zhang et al ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, video-assisted thoracic surgery (VATS) is superior to open thoracotomy for the resection of early stage NSCLC, with the advantages of less complications, less pain, faster recovery and equivalent long-term survival ( 8 11 ); however, several recent case series and anecdotal reports have suggested that VATS following neoadjuvant chemotherapy could also achieve satisfactory outcomes in locally advanced NSCLC patients ( 2 , 12 14 ). But there was little evidence suggesting the feasibility and safety of VATS after neoadjuvant chemoimmunotherapy in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who underwent RATS were associated with the shortest operation duration (RATS 100.85 ± 29.06 vs VATS 113.75 ± 33.40 vs OL 112.76 ± 22.85 mins, p <0.001) and the least blood loss (p <0.001). RATS also led to the shortest ICU stay (RATS 0[0-1] vs VATS 1[0-1] vs OL 1[0-1] days, p = 0.004), chest tube drainage duration (RATS 4 [3][4][5][6] vs VATS 5 [4][5][6] vs OL 5 [5][6][7] days, p <0.001) and postoperative stay (RATS 5 [4][5][6] vs VATS 5 [4][5][6][7] vs OL 6 [5][6][7][8] days, p <0.001) among three surgical approaches, and had a similar conversion rate compared with VATS (p = 0.184). However, the overall cost in the RATS group was $14838.26 ± 2841.65, which was significantly higher than that in the VATS ($13190.51 ± 2120.18, p <0.001) and OL ($13429.58 ± 2582.36, p <0.001) group.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…Although open lobectomy (OL) is still the standard surgical approach for resectable NSCLC, it is associated with considerable postoperative complications and even surgeryrelated mortalities, especially in elderly patients (6). Thus, minimally invasive surgeries (MISs) which could reduce postoperative complications and shorten postoperative hospital stay, such as video-assisted thoracoscopic surgery (VATS), have been widely adopted (7). Numerous studies have suggested that VATS achieved better perioperative outcomes and similar longterm survival compared to OL for older NSCLC patients (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Lobectomy with systematic mediastinal lymph node dissection is the gold standard surgical treatment for early non-small cell lung cancer (NSCLC) ( 1 ). Lobectomy performed by video-assisted thoracoscopic surgery (VATS) has been shown to reduce postoperative pain, inflammatory response, and length of hospital stay ( 2 ). Although the overall mortality from lobectomy has declined to approximately 0.5–1% with the improvement of surgical techniques and perioperative management ( 3 ), the morbidity after lobectomy for lung cancer remains between 26.0% and 54.7% ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%